2015
DOI: 10.1158/0008-5472.can-14-3502
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Rationale to Target PTEN-Deficient Tumor Cells with Inhibitors of the DNA Damage Response Kinase ATM

Abstract: Ataxia telangiectasia mutated (ATM) is an important signaling molecule in the DNA damage response (DDR). ATM loss of function can produce a synthetic lethal phenotype in combination with tumor-associated mutations in FA/BRCA pathway components. In this study, we took an siRNA screening strategy to identify other tumor suppressors that, when inhibited, similarly sensitized cells to ATM inhibition. In this manner, we determined that PTEN and ATM were synthetically lethal when jointly inhibited. PTEN-deficient ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 20 publications
5
55
0
Order By: Relevance
“…Investigators have unraveled a set of candidate gene targets hypothetically resulting in synthetic lethality. HNF, ARID1A, ATR, ATM, Chk1 and PTEN may be the key genes in CCC (18,32,47,52,55). Notably, the HNF-Chk1 axis was specifically upregulated in CCC (18).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Investigators have unraveled a set of candidate gene targets hypothetically resulting in synthetic lethality. HNF, ARID1A, ATR, ATM, Chk1 and PTEN may be the key genes in CCC (18,32,47,52,55). Notably, the HNF-Chk1 axis was specifically upregulated in CCC (18).…”
Section: Discussionmentioning
confidence: 95%
“…siRNA screening strategies identified PTEN and ATM as synthetically lethal partners (55). One preclinical study demonstrated that ATM inhibition resulted in DNA damage, cell cycle arrest and apoptosis specifically in PTEN-deficient cells (55).…”
Section: Synthetic Lethal Partners In CCCmentioning
confidence: 99%
“…PTEN-deficient cells were found to arrest in the mitotic part of the cell cycle and demonstrated DNA aberrations consistent with catastrophic DNA damage 7 that led to apoptotic cell death (Fig. 1).…”
mentioning
confidence: 95%
“…Importantly, this toxic effect is specific to the cancer cell in that loss of ATM function or the FA/BRCA pathway alone is not lethal, a phenomenon referred to as "synthetic lethality." 6 In our current publication 7 we have extended this work to look for synthetic lethal interactions between ATM and other TSGs. We used siRNA screening to individually knockdown 178 TSGs in paired ATM functional and nonfunctional cell lines and identified potential synthetic lethal interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation